2018
DOI: 10.1016/j.jns.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

S100B, NSE and MMP-9 fail to predict neurologic outcome while elevated S100B associates with milder initial clinical presentation after aneurysmal subarachnoid hemorrhage

Abstract: None of the measured biomarkers were associated with the neurological outcome evaluated at six months after aSAH. Elevated levels of S100B in patients with non-severe initial presentation suggest an adaptive role of this biomarker in aSAH. Based on our findings it is not advisable to use these biomarkers to guide clinical decision-making in patients with aSAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Importantly, early S100B measurements predicted patient mortality 3-4 days before high intracranial pressure (ICP) readings predicted the same. Quite the opposite results were documented recently by Kiiski et al, who found that elevated S100B at day 1 was strongly associated with a less severe initial clinical representation of aSAH, and the study concluded that plasmatic biomarkers should not be used to guide clinical decision-making in patients with aSAH, in prognostication based on S100B [3].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Importantly, early S100B measurements predicted patient mortality 3-4 days before high intracranial pressure (ICP) readings predicted the same. Quite the opposite results were documented recently by Kiiski et al, who found that elevated S100B at day 1 was strongly associated with a less severe initial clinical representation of aSAH, and the study concluded that plasmatic biomarkers should not be used to guide clinical decision-making in patients with aSAH, in prognostication based on S100B [3].…”
Section: Discussioncontrasting
confidence: 54%
“…On admission, patients were assessed using the Glasgow Coma Scale (GCS). Subarachnoid haemorrhage severity was evaluated with the Hunt and Hess (H-H) scale and defined as severe (4-5) or moderate (1)(2)(3). The extent of haemorrhaging was assessed with a computerized tomography (CT) scan of the head and classified using the Fisher scale, where 1 = no subarachnoid (SAH) or intraventricular haemorrhage (IVH) detected, 2 = diffuse thin (<1 mm) SAH, no clots, 3 = localized clots and/or layers of blood >1 mm in thickness, no IVH, and 4 = diffuse or no SAH an intracerebral or intraventricular clot.…”
Section: Clinical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite opposite results have recently been published. Kiiski et al [ 30 ] found that S100B and NSE measured during the first 24 h were not associated with neurological outcome evaluated at 6 months after an aSAH. Similar results were published by Olivecrona et al [ 31 ]; based on the biomarker concentrations determined twice daily for five consecutive days, there was no significant clinical value of S100B and NSE as predictors of clinical outcome at 3 and 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial aneurysmal subarachnoid haemorrhage (aSAH) is an acute cerebral vascular disease that severely damages the central nervous system and has pathological effects on multiple organs in the body. Wang (2015) and Xu, Wang, Hu, and Liang (2015) stated that the aSAH patient has rapid onset, critical symptoms, volatile conditions, difficult nursing and 50% mortality rate after onset within 1 year (Kiiski et al, 2018), which suggests higher demand for nursing.…”
Section: Introductionmentioning
confidence: 99%